أثر الفسادعلى جاذبية الدول العربية للاستثمار الأجنبي المباشر - دراسة قياسية بإستخدام نماذج بانل للفترة 2003-2016 - طير, عبدالحق; ريمي, عقبة; غريب, بولرباح (University of Eloued جامعة الوادي, 2019)
حاولت الدراسة، قياس أثر الفساد على جذب الاستثمار الأجنبي المباشر في الدول العربية (10 دول)، وذلك باستخدام نماذج بانل للفترة (2003-2016)، وقد تم اختيار هذه الدول بناء على توافر المعطيات والبيانات الخاصة بمتغيرات وفترة الدراسة، وقد اعتمدت على بيانات تقرير مناخ الاستثمار الصادر عن المؤسسة العربية لضمان الاستثمار فيما يخص الاستثمار الأجنبي المباشر، ومؤشر مدركات الفساد الصادر عن منظمة الشفافية العالمية فيما يتعلق بالفساد. هذا بإضافة متغيرات اقتصادية وأخرى في النموذج كمتغيرات مستقلة ذات علاقة مباشرة بالمتغير التابع، وبناء على نتائج تقدير النموذج توصلت الدراسة إلى أن متغير الفساد كان له علاقة معنوية وعكسية، أي له تأثير سلبي، بحيث وجد أنه كلما زاد حجم الفساد بنسبة 1% انخفض حجم تدفق الاستثمار الأجنبي المباشر في الدول العربية بنسبة 1.47% Abstract: The study attempted to measure the impact of corruption on attracting foreign direct investment in 10 Arab countries by using PANEL models for the period (2003-2016). These countries were selected on the basis of the availability of data and information on the variables and the period of the study. It relied upon the report data of the investment climate issued by the Arab Investment Guarantee Corporation concerning Foreign Direct Investment, and Corruption Perceptions Index issued by the International Transparency Organization on corruption. In addition, Economic and other variables were added to the model as independent variables directly related to the dependent one. Based on the results of the model's estimation, the study concluded that the variable of corruption had a significant and inverse relationship; I.e it has a negative impact, so that the higher the level of corruption by 1% is, the lower the level of the flow of Foreign Direct Investment in the Arab countries decreased by 1.479%.
The Impact of Corruption on the Attractiveness of Arab Countries to the Foreign Direct Investment: An Empirical Study Using PANEL Models for the Period 2003-2016
مقال - مجلة رؤى اقتصادية
Keywords: الفساد الاستثمار الأجنبي المباشر بانل; Corruption, Foreign Direct Investment, PANEL models, Arab Countries. Jel Classification Codes: F21